Achromobacter xylosoxidans Relapsing Peritonitis and Streptococcus suis Peritonitis in Peritoneal Dialysis Patients: A Report of Two Cases. (30th July 2018) - Donderski, Rafał; Grajewska, Magdalena; Mikucka, Agnieszka; Sulikowska, Beata; Gospodarek-Komkowska, Eugenia; Manitius, Jacek
Abstract : Peritonitis is considered to be the most common complication of peritoneal dialysis (PD). It is usually caused by Gram positive Staphylococcus epidermidis. Achromobacter xylosoxidans (A. xylosoxidans) and Streptococcus suis (S. suis) are rare pathogens, but there is emerging evidence that they may be also responsible for PD related peritonitis. We described 2 cases of rare peritonitis treated in our center. In our opinion this is the first described case of PD related peritonitis caused by Streptococcus suis.